2017
DOI: 10.1101/168815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytokinin signaling inMycobacterium tuberculosis

Abstract: SummaryIt was reported the human-exclusive pathogen Mycobacterium (M.) tuberculosis secretes cytokinins, which previously had only been known as plant hormones. Cytokinins are adenine-based signaling molecules in plants that have never been shown to participate in signal transduction in other kingdoms of life. Here, we show that cytokinins induce the strong expression of the M. tuberculosis gene, Rv0077c. We found that a TetR-like transcriptional regulator, Rv0078, directly repressed expression of the Rv0077c … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…CK‐nucleosides are converted to free‐base forms by Lonely Guy (LOG) proteins that encode a cytokinin riboside 5′‐monophosphate phosphoribohydrolase (Kurakawa et al ., ). These enzymes have been described in detail in plants such as Arabidopsis thaliana and Oryza sativa , and in bacteria such as Mycobacterium tuberculosis (Samanovic et al ., ) and Corynebacterium glutamicum (Seo and Kim, ). Interestingly, strain MSR2 possesses one gene encoding a LOG family protein (CTZ24_24430) present in plasmid pMSR2C, which has a high identity to the described LOGs of plants (~47.5%) and bacteria (47.3%).…”
Section: Resultsmentioning
confidence: 99%
“…CK‐nucleosides are converted to free‐base forms by Lonely Guy (LOG) proteins that encode a cytokinin riboside 5′‐monophosphate phosphoribohydrolase (Kurakawa et al ., ). These enzymes have been described in detail in plants such as Arabidopsis thaliana and Oryza sativa , and in bacteria such as Mycobacterium tuberculosis (Samanovic et al ., ) and Corynebacterium glutamicum (Seo and Kim, ). Interestingly, strain MSR2 possesses one gene encoding a LOG family protein (CTZ24_24430) present in plasmid pMSR2C, which has a high identity to the described LOGs of plants (~47.5%) and bacteria (47.3%).…”
Section: Resultsmentioning
confidence: 99%
“…There are only a few studies on the role of this family of molecules that is similar to a phytohormone influencing plant growth and development [60]. Some have shown that it can influence signaling in M. tuberculosis [69] whereas others have discovered that cytokinin accumulation is conditionally deleterious as it can lead to an aldehyde breakdown product that kills mycobacteria in the presence of nitric oxide produced by macrophages [59]. It remains to be tested if evolution has sacrificed, in a biological tradeoff, the growth speed of the slowgrowing mycobacteria by altering, for example, the cytokinin pathway, in order to allow a better survival in macrophages or other types of macrophage-like cells such as amebae.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CK signalling was elucidated in bacteria [ 244 , 265 ]. The receptor from Xanthomonas campestris pv.…”
Section: Cytokinin Signallingmentioning
confidence: 99%
“…In the human pathogen Mycobacterium tuberculosis , CK induces the formation of a lipid-like molecule, which binds to a repressor and de-represses the expression of a responsive gene. However, unlike canonical CK signalling, the Mycobacterium one is significantly inhibited by adenine [ 265 ].…”
Section: Cytokinin Signallingmentioning
confidence: 99%